2012
DOI: 10.3141/2301-08
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Economic Impacts of Converting Two-Way Frontage Roads to One-Way Operation

Abstract: In some states (e.g., Texas), frontage roads have been a design solution for providing access along rural freeways and access-controlled principal arterials. In rural and lesser-developed urban areas, the frontage roads are usually operated as two-way facilities because of relatively long distances between interchanges. As areas become more urban and the adjacent land is developed, traffic volumes increase, and as interchange spacing decreases, it becomes desirable to convert the frontage roads to one-way oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The perception of these property owners is that limiting access is detrimental to business. Previous research has shown that access management projects generally do not have negative long-term effects on land values and business vitality along a corridor (2,4,5). Although these findings are valuable and insightful, especially for large-scale, corridorwide projects, they are difficult to apply to access decisions about a specific parcel of land.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The perception of these property owners is that limiting access is detrimental to business. Previous research has shown that access management projects generally do not have negative long-term effects on land values and business vitality along a corridor (2,4,5). Although these findings are valuable and insightful, especially for large-scale, corridorwide projects, they are difficult to apply to access decisions about a specific parcel of land.…”
mentioning
confidence: 86%
“…In Iowa, a similar study using corridor data and business surveys also showed that access management did not have a negative long-term impact on business vitality, and in some cases actually improved the business environment (7). A more recent study by Eisele et al also used surveys and appraised land values to evaluate the long-term economic impacts of converting frontage roads from two-way to one-way operations (5). Again, the findings showed that the access management projects…”
Section: Economic Impactsmentioning
confidence: 99%
“…In other words, the pedestrian crash frequency at intersections of two one-way streets was roughly half of that at other intersections. In the same study described above, Eisele et al also conducted a before-after evaluation of intersections that were located on freeway frontage roads that were converted from two-way operation to one-way operation (2). They proposed the CMFs listed in Table 3 for different subsets of intersection-related KABC crashes.…”
mentioning
confidence: 99%
“…Eisele et al conducted a before–after evaluation of freeway frontage roads that were converted from two-way operation to one-way operation ( 2 ). They proposed a crash modification factor (CMF) of 0.43 for fatal, incapacitating injury, non-incapacitating injury, and possible injury crash (KABC, respectively) segment-related crashes for frontage road conversions, meaning that the average reduction in fatal and injuries (FI) crashes on frontage road segments following a conversion is 57% (or 1.00−0.43, expressed as percent).…”
mentioning
confidence: 99%